A trout (Oncorhynchus mykiss) perfusion model approach to elucidate the role of blood removal for lipid oxidation and colour changes in ice‐stored fish muscle. (17th January 2020) - Harrysson, Hanna; Swolin, Birgitta; Axelsson, Michael; Undeland, Ingrid
Summary: Whole body saline‐perfused rainbow trout ( Oncorhynchus mykiss ) was ice‐stored for 4 weeks and compared with unwashed/washed minces from unbled and bled trout in terms of rancid odour, peroxide value (PV), thiobarbituric acid reactive substances (TBARS) and redness loss. Muscle from saline‐perfused fish, which had 72% less total haem, was deficient in rancid odour during the whole storage, while bled (54% less haem) and unbled samples developed rancid odour already after 4 and 2 days; higher intensity without bleeding. PV/TBARS also developed in the order unbled > bled > perfused samples; however, PV/TBARS were not as completely prevented as rancid odour after perfusion. Saline washing (3 × 3 volumes) of unbled mince removed 84% haem and yielded the second most stable sample while saline washing (1 × 1 volumes) destabilised unbled mince, despite 64% haem removal. Concurrent antioxidant removal during washing of minces obviously counteracted the effect of blood removal and washing fish mince with small volumes of solution should be used with great care. Abstract : Using saline‐perfused trout ( Oncorhynchus mykiss ) as a model, a profound impact from blood removal on rancid odour development in ice stored minced fish muscle was observed. Classic bleeding via gill cut, as well as washing of mince from unbled fish with 3 × 3 volumes of saline only partially prevented lipid oxidation, including rancid odour. Washing mince with a small amount of saline (1 × 1 volume) slightly stimulated oxidation; most likely due to removal of more anti‐ than pro‐oxidants.